Biofloc technology significantly reshapes water microbiome and improves survival rates in Japanese eel (Anguilla japonica) - Jiho Yang; Hyunjun Choi; Jun Seong Park; Yehyeon Cha; Ju-Ae Hwang; Seung-Yoon Oh (Microbiology Spectrum)
ABSTRACT Global aquaculture production faces the challenge of biologically cycling nitrogenous waste. Biofloc technology (BFT) systems offer the potential to reduce water consumption and eliminate waste products by using beneficial microorganisms to convert waste into usable nutrients or non-toxic molecules. Unlike flow-through systems (FTS), which depend on continuous water exchange and result in higher operational costs as well as limited microbiome stability, BFT operates without the need for constant water exchange. Instead, it leverages its inherent microbiome for nutrient recycling, which can help reduce associated costs. The Japanese eel (Anguilla japonica), consumed as a luxury food item in China, Japan, and South Korea, has seen little research related to BFT. In this study, we observed the survival and growth rates of eels treated with BFT over 8 weeks and monitored changes in the gut and water microbiome using 16S rRNA amplicon sequencing (metabarcoding) and quantitative PCR. Our research demonstrated that BFT treatment was more advantageous for eel growth compared with FTS in terms of eel survival rate, feed intake amount, and growth rate. Both treatments did not result in water quality conditions detrimental to the growth of eels. Alpha diversity was higher in BFT water microbiome than in FTS, but no differences were observed in the guts of eels between the two treatments. While community structures of water microbiome (taxonomic composition) differed between BFT and FTS, gut microbiome did not. To identify the operational taxonomic units (OTUs) that directly influence the feed consumption rate of eels, closely linked to their growth rate, we first determined the differentially abundant residents and then highlighted the most informative OTUs. In summary, our analysis identified microbial residents potentially associated with the higher growth rates observed in BFT-treated eels, highlighting the need for further functional studies.IMPORTANCEThis study is significant as it addresses a critical gap in the application of Biofloc Technology (BFT) to Japanese eel (Anguilla japonica) aquaculture, a high-value species in East Asia. BFT’s potential to reduce water consumption and enhance growth through the use of beneficial microorganisms presents a sustainable solution to the challenges of nitrogenous waste management in global aquaculture. Our research provides the first comprehensive analysis of how BFT influences both the growth and microbiome composition of Japanese eels compared with traditional flow-through systems. By identifying specific microbial residents potentially linked to improved feed consumption and growth, this study opens new avenues for optimizing BFT in eel farming. The findings contribute to the broader understanding of microbial roles in aquaculture, highlighting the potential for BFT to support more sustainable and productive aquaculture practices.